Partisipasi Masyarakat Dalam Pengelolaan Hutan Mangrove di Desa Alang-Alang Kabupaten Tanjung Jabung Timur Provinsi Jambi - Junwalki Junwalki; Donwill Panggabean; Albert Gamot Malau (Dinasti Research, 2025)
Sustainable mangrove management requires community efforts and participation. Where positive community perceptions of the existence of mangroves will increase community participation in mangrove management activities. Several factors that encourage the community to participate are both internal and external factors. This study aims to see the perception and participation of the community towards the mangrove forest ecosystem and recommend sustainable mangrove forest management strategies. The study was conducted from August to September 2024 using qualitative research methods by collecting descriptive data in written or oral form, which were then interpreted descriptively holistically, contextually using researchers as the main instrument for collecting data. To formulate a mangrove management strategy for the sustainability of the mangrove ecosystem, a SWOT (Strengths, Weaknesses, Opportunities and Treaths) analysis was carried out. The results of the study showed that the Alang-Alang Village community had a good and positive perception of the existence of the mangrove forest ecosystem, but their participation was still passive (participating if there was someone to accommodate and not yet their own initiative) in the management and preservation of mangrove forests. Where good community perception and community participation also influenced the good ecology of the Alang-Alang Village mangrove forest, including the area and density of good mangroves. However, there are still individuals from other villages who sometimes still cut down mangrove trees and added high waves and strong tidal currents also damage the existing mangrove forest ecosystem. For the management of the mangrove forest ecosystem, Alang-Alang Village is in quadrant I, where the strategy that can be applied in this condition is to support an aggressive strategy or aggressive growth policy (Growth oriented strategy) by utilizing existing strengths and opportunities